Reconstruction of Rationality in Islamic Philosophy and Theology: Harun Nasution’s Thought and Its Relevance to Contemporary Islamic Studies in Indonesia - Muama, Avisena Perdana Putra; Tahawi, Abdelrahman Moawad Ali (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This study aims to analyze Harun Nasution's rational approach to Islamic philosophy and theology, as well as its relevance to contemporary Islamic studies in Indonesia. This rational approach is considered crucial for overcoming the exclusivism and dogmatism prevalent among Indonesian Muslims. The methodology employed is a qualitative-analytical approach utilizing library research, which facilitates an in-depth examination of Harun Nasution’s thought through various literary sources. The results indicate that, first, Harun Nasution perceives philosophy in Islam as a means to counter the stagnation of religious thought. His rational approach to philosophical studies is grounded in critical, free, and logical thinking. Philosophy serves as a tool to deeply explore Islamic teachings, both absolute and relative, enabling Muslims to break free from dogmatism and exclusivism in religion. Second, in the realm of theology, Harun critiques orthodox Islamic theological thought, particularly regarding the roles of reason and human free will, which are often constrained by dogmatism and literalism in the interpretation of the Qur’an. He proposes a new approach known as rational theology, which emphasizes the significance of reason and human freedom in comprehending religious teachings. The implications of this study underscore the importance of adopting a rational approach in Islamic studies in Indonesia. This approach enables Muslims to optimally enhance creativity and productivity across various aspects of life while simultaneously mitigating dogmatic and exclusive attitudes.Abstrak: Penelitian ini bertujuan menganalisis pendekatan rasional Harun Nasution dalam filsafat dan teologi Islam serta relevansinya bagi studi Islam kontemporer di Indonesia. Pendekatan rasional ini dipandang penting untuk mengatasi sikap eksklusivitas dan dogmatisme yang berkembang di kalangan umat Muslim Indonesia. Metode yang digunakan adalah kualitatif-analitis dengan jenis penelitian kepustakaan, yang memungkinkan kajian mendalam terhadap pemikiran Harun Nasution melalui sumber-sumber literatur. Hasil penelitian menunjukkan bahwa, Pertama, Harun Nasution memandang filsafat dalam Islam harus berperan melawan stagnasi pemikiran keagamaan. Pendekatan rasional yang digunakannya dalam kajian filsafat didasarkan pada berpikir kritis, bebas, dan logis. Filsafat berfungsi sebagai alat untuk menyelidiki secara mendalam ajaran Islam yang bersifat mutlak maupun relatif, sehingga umat Islam tidak lagi terbelenggu oleh dogmatisme dan eksklusivitas dalam beragama. Kedua, dalam bidang teologi, Harun mengkritik pemikiran ortodoksi teologi Islam klasik, khususnya terkait kedudukan akal dan kehendak bebas manusia yang dibatasi oleh sikap dogmatisme dan literalisme dalam memahami Al-Qur’an. Harun menawarkan pendekatan baru yang disebut teologi rasional, yang menekankan pentingnya akal dan kebebasan manusia dalam memahami ajaran agama. Implikasi dari kajian ini adalah pentingnya penerapan pendekatan rasional dalam studi Islam di Indonesia agar umat Muslim dapat mengembangkan kreativitas dan produktivitas secara optimal di berbagai bidang kehidupan, sekaligus mengurangi sikap dogmatis dan eksklusif.